Inclusion of people with disabilities in the processes of integral professional training at the Center for Industrial Automation, Regional Caldas - SENA - Orozco, Carlos Eduardo
During the year 2016, an investigation was undertaken with the purpose of identifying the weaknesses and strengths of the SENA Industrial Automation Center, Caldas Regional, to provide comprehensive vocational training for people with visual, physical and hearing disabilities. The methodology used corresponded to a quasi-experimental research with a qualitative approach, developed in four phases: analysis, planning, execution and evaluation; carried out by the Electronic Research, Automation and Renewable Energies Group. As a result, there are active didactic strategies that allow the learning paths of the selected programs to be inclusive.